Massive cerebral edema resulting in brain death as a complication of Cryptococcus neoformans meningitis - Jose Orsini; Christa Blaak; Dalia Mahmoud; Jeong Young-Gwang (Greater Baltimore Medical Center, 2015)
Despite the widespread use of highly active antiretroviral therapy, cryptococcal meningoencephalitis has emerged as the second leading cause of infectious morbidity and mortality in HIV-infected patients worldwide. It presents usually as subacute or chronic disease but occasionally may be fulminant. Common clinical presentations included headache, fever, and depressed level of consciousness. The infection affects both the subarachnoid space and brain parenchyma, and is characterized by a paucity of inflammation and a large fungal burden in the cerebrospinal fluid at the time of diagnosis. Infection is usually lethal without treatment, thus the prompt diagnosis and therapy might improve the outcome. We report a case of brain death caused by Cryptococcus neoformans meningitis that was diagnosed based on clinical neurological examinations and supported by the absence of cerebral blood flow on brain angiography.